PENGARUH GAYA KEPEMIMPINAN DAN FAKTOR LAINNYA TERHADAP KINERJA KARYAWAN BACKOFFICE PT. X - RAMADHAN, RANIAH PUTRI; SANTOSO, WAWA (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
The lack of attention from service-oriented companies towards the work environment can lead to a decline in employee performance. This research aims to investigate the extent to which these conditions result in optimal employee performance. The data analysis method employed is Structural Equation Modeling (SEM) using the SmartPLS version 3.3.9 tool, involving variables such as leadership style, motivation, compensation, work environment, and job satisfaction in relation to employee performance. The research focuses on the Back Office of PT X with 104 employees as samples. The findings indicate that leadership style and the work environment have a positive impact on employee performance, whereas motivation, compensation, and job satisfaction do not have a significant influence. Recommendations for PT. X include strengthening the implementation of existing leadership styles and improving the work environment to support employee productivity.